Tire sidewall rubber composition for reducing rolling resistance of tire
By using specific types and amounts of carbon black, as well as silane coupling agent and other components in the sidewall rubber composition, an appropriate dedimensional structure is formed, and the problem of reducing modulus and hardness when reducing the rolling resistance of the tire in the prior art is solved, and a safer and more efficient tire performance is achieved.
Patent Information
- Application Number
- CN202411979923.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
When the prior art reduces the rolling resistance of the tire, it is easy to cause the material modulus and hardness to decrease, thereby losing the sidewall anti-flexural performance, affecting the safety of the tire.
A new sidewall rubber composition is adopted, including cis-1,4 polyisoprene, butadiene rubber, low-hysteresis carbon black, gas-phase white carbon black, silane coupling agent and other components. By adjusting the type and dosage of the carbon black, a fractal structure of no less than 20μm and a fractal structure of several hundred nanometers are formed, and the dynamic performance and reinforcement performance of the rubber are improved.
It effectively reduces the tire rolling resistance, while maintaining the modulus and hardness of the glue, improving the sidewall anti-flexion performance, and improving the tire safety and fuel efficiency.
Smart Images

Figure CN119751996A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tire materials, in particular to a sidewall rubber composition for reducing tire rolling resistance. Background Art
[0002] When the rolling resistance of the tire is reduced by about 10%, the motor vehicle will save about 1.2% of fuel, so rolling resistance is an extremely important characteristic. The distribution of the rolling resistance of the radial tire in various parts is: 49% for the tread, 14% for the sidewall, and 11% for the carcass. The sidewall is the semi-component that has a greater impact on the rolling resistance of the tire except for the tread. The rolling resistance of the tire is closely related to the dynamic heat generation of the rubber. On the one hand, the dynamic compression heat generation of the rubber is related to the friction between the fillers inside the rubber, the friction between the fillers and the rubber macromolecular chains, and the friction between the rubber macromolecular chains; on the other hand, it is believed that it is related to the viscoelastic hysteresis of the rubber, that is, when the rubber undergoes periodic strain, the particle network is destroyed-reconstructed. This destruction-reconstruction is a hysteresis process, which will cause dynamic heat generation inside the rubber. Usually, we use the loss factor tanδ value of the rubber at 60°C of the dynamic thermodynamic spectrometer to simply characterize the rolling resistance of the tire. The lower the value, the lower the rolling resistance, and vice versa. The higher the rebound value, the better the rebound resilience is tested with a rebound tester.
[0003] Among the current methods for reducing rolling resistance, reducing the amount of reinforcing filling system will reduce the modulus and hardness of the rubber compound. For the sidewall, the anti-flexing performance will also be lost, which is not conducive to ensuring the safety of the tire.
[0004] Based on this, a sidewall rubber composition for reducing tire rolling resistance is now provided, which can eliminate the disadvantages of the existing device. Summary of the invention
[0005] The purpose of the present invention is to provide a sidewall rubber composition for reducing the rolling resistance of a tire, thereby solving the problem of insufficient tire safety in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A sidewall rubber composition for reducing the rolling resistance of a tire comprises, by weight: 40-60 parts of cis-1,4 polyisoprene, 40-60 parts of butadiene rubber, 20-40 parts of carbon black, 10-20 parts of novel white carbon black, 0-2 parts of silane coupling agent, 1-3 parts of stearic acid, 2-7 parts of zinc oxide, 1.5-3.5 parts of antioxidant 6PPD, 0.5-3 parts of antioxidant TMQ, 2 parts of antioxidant 31000, 1.5-2 parts of oil-extended sulfur powder and 0-1.5 parts of accelerator.
[0008] On the basis of the above technical solution, the present invention also provides the following optional technical solution:
[0009] In one alternative: the butadiene rubber is 50 parts.
[0010] In an optional embodiment: the carbon black is low hysteresis carbon black.
[0011] In an optional embodiment: the specific surface area of carbon black is between 11-22 g / kg, and the oil absorption value is between 90-10010-5 m3 / kg.
[0012] In an optional solution, the novel silica is fumed silica.
[0013] In one alternative: the nitrogen adsorption specific surface area of fumed silica is between 15-35 m2 / g and the silica content is above 95.0%
[0014] In an optional solution, the silane coupling agent is 1%-10% by weight of the white carbon black.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] In this application, the type of carbon black is changed, the amount of carbon black is reduced and part of the carbon black is replaced by white carbon black. The carbon black particle aggregates formed in the polymer matrix are rotatable ellipsoidal shapes, which are used as basic units to form a fractal structure of not less than 20 μm. The white carbon black forms a white carbon black aggregate with a fractal structure of several hundred nanometers in the polymer matrix. The white carbon black filled rubber is easily distributed with deformation. During the deformation process, friction is not easy to occur between the white carbon black aggregates, so the hysteresis loss of the rubber composite material can be reduced, and the dynamic properties of the rubber material are improved. At the same time, the addition of white carbon black greatly improves the reinforcement performance, and the modulus and hardness are guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the interaction between the materials of the present invention.
[0018] Notes on figure numbers: a. Friction between polymer chains; b. Friction between filler particles; c. Friction between filler and macromolecules. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] like Figure 1As shown, an embodiment of the present invention provides a sidewall rubber composition for reducing tire rolling resistance, which comprises, by weight:
[0021] 40-60 parts by weight of cis-1,4 polyisoprene, 40-60 parts by weight of butadiene rubber, 20-40 parts by weight of carbon black, 10-20 parts of new white carbon black, 0-2 parts by weight of silane coupling agent, 1-3 parts by weight of stearic acid, 2-7 parts by weight of zinc oxide, 1.5-3.5 parts by weight of antioxidant 6PPD, 0.5-3 parts by weight of antioxidant TMQ, 0-2 parts by weight of antioxidant 3100, 1.5-2 parts by weight of oil-extended sulfur powder, 0-1.5 parts by weight of accelerator CZ:
[0022] Natural rubber refers to latex, 5# natural rubber, 10# natural rubber, 20# natural rubber, and composite rubber commonly used in the rubber industry, including the tire industry and product industry. The origin is generally from Thailand, Vietnam, Africa, China, Malaysia, etc., and 50-80 parts by weight of 20# natural rubber is preferably used;
[0023] Preferably 20-40 parts by weight of low hysteresis carbon black, the specific surface area (iodine absorption value) of the carbon black is between 11-22 g / kg, and the oil absorption value is between 90-10010-5 m3 / kg;
[0024] Preferably, 10-20 parts by weight of the novel silica is fumed silica, which has a nitrogen adsorption specific surface area of 15-35 m2 / g and a silicon dioxide content of more than 95.0%;
[0025] Others: 1-3 parts by weight of stearic acid, 2-7 parts by weight of zinc oxide, 1.5-4.5 parts by weight of antioxidant 6PPD, 0.5-3.5 parts by weight of antioxidant TMQ, 1.5-2 parts by weight of oil-extended sulfur powder, 0.5-2.5 parts by weight of accelerator CZ, all of which are commonly used materials for tire manufacturing;
[0026] The mixing process is as follows:
[0027] First-stage mixing: the rotor speed is 45-55rpm, the upper push bolt pressure is 0.55MPa, the raw rubber is plasticized, pressed for 10-20s and then lifted, small medicine is added and pressed for 15-25s, oil materials are added at the same time, pressed for 10-30s and then lifted, and then pressed to 145-165℃ to discharge the glue, to obtain a first-stage masterbatch and cool it down;
[0028] Final refining and mixing: the rotor speed is 20-30rpm, the upper push bolt pressure is 0.4MPa, the masterbatch prepared and parked for 4-72h is added together with sulfur and accelerator, the ball is lifted after pressing for 15-25s, the ball is lifted after pressing for 15-25s, the ball is pressed to 90-100℃ to discharge the glue, and the invention mixture is obtained, and it is cooled and parked.
[0029] Rubber material physical property test: After calendering in sheet form, the samples for testing physical properties are formed, and the relevant physical, mechanical and dynamic properties are tested after vulcanization at 151°C for 30 minutes. The physical and mechanical properties are all implemented in accordance with national standards, and the dynamic properties are obtained by temperature scanning using a dynamic viscoelastic spectroscopy instrument produced by GABO, Germany. The test conditions are compression mode: dynamic strain is 5%, static strain is 0.2%, frequency is 10Hz, and heating rate is 2°C / min.
[0030] The kneading according to the above-mentioned kneading method will be specifically described below based on the examples of the present invention, but the present invention is not limited to these examples.
[0031] Following the analytical data in Table 1, the comparative example is a sample of carbon black N550, and the inventive example is a sample of carbon black with a large particle size. The comparative example is not used in the present invention.
[0032] For the testing of the above samples, the following test methods were used:
[0033] The oil absorption value is tested according to the manual method of GB / T 3780.2 or ASTM D2414.
[0034] The compression oil absorption value test is carried out according to GB / T 3780.4 or ASTM D3493.
[0035] According to ASTM D1510, a sample weighing 0.5000g was tested for iodine absorption value.
[0036] Conduct external specific surface area (STSA) test according to GB / T 10722 or ASTM D6556;
[0037] Table 1 Chemical indexes of large particle size carbon black of the invention example;
[0038] Test items unit Comparative Example Invention Example Oil absorption value <![CDATA[10 -5 m 3 / kg]]> 123 96 Compression oil absorption value <![CDATA[10 -5 m 3 / kg]]> 85 66 Iodine absorption value g / kg 43 15 External specific surface area (STSA) <![CDATA[10 3 m 2 / kg]]> 41 22
[0039] Table 2 Chemical indexes of white carbon black in the invention example;
[0040] Test items unit Invention Example Specific surface area (BET) <![CDATA[m 2 / g]]> 25 Silica content % 96.9 Oil absorption value <![CDATA[cm 3 / g]]> 1.6 Specific surface area (CTAB) <![CDATA[10 3 m 2 / kg]]> 30
[0041] Detect the oil absorption value. The higher the test value, the higher the primary structure and the higher the reinforcement performance.
[0042] Test the compression oil absorption value. The higher the test value, the higher the secondary structure and the higher the reinforcement performance.
[0043] Detect the iodine absorption value. The lower the test value, the larger the particles are and the less heat they generate.
[0044] Detect the external specific surface area (STSA) value. The lower the test value, the larger the particle size and the lower the heat generation.
[0045] Compared with the comparative example, the most obvious characteristics of the inventive example are smaller specific surface area and larger particle size;
[0046] Following the formulation of Table 2, the rubber compositions are referred to herein as Invention Example 1, Invention Example 2, and Invention Example 3. The comparative examples are not used in the present invention;
[0047] Payne effect, Mooney viscosity and Mooney scorch final rubber are directly tested, and other test samples are produced by vulcanization. The vulcanization conditions are 151°C for 30 minutes, and vulcanization is carried out on a flat vulcanizer to obtain a 2mm thick vulcanized rubber sheet. High temperature thermal oxidation aging conditions: temperature 100°C, time is 48 hours. The obtained vulcanized rubber sheet is used for the following experiments. And these test samples are used to determine the typical material properties for the rubber industry. For the testing of the above test samples, the following test methods are used:
[0048] According to GB / T 528, tensile strength and elongation at break at room temperature.
[0049] According to GB / T 3512, hot air aging is performed;
[0050] Table 3 Invention example scheme;
[0051]
[0052]
[0053] Test the tensile strength value. The higher the test value, the better the strength.
[0054] Test the elongation value. The higher the test value, the better the fatigue resistance and chipping resistance. Test the modulus value. The higher the test value, the higher the modulus and the higher the reinforcement performance of carbon black. Test the tanδ at 60℃. The lower the test value, the lower the heat generation and the smaller the rolling resistance.
[0055] Table 4 Basic physical properties data
[0056]
[0057]
[0058] Detect the G' value. The lower the test value, the better the filler dispersion.
[0059] Test the Mooney viscosity value. The lower the test value, the better the processing performance.
[0060] Test the Mooney scorch value. The higher the test value, the better the processing safety.
[0061] Table 5 Rubber processing properties;
[0062] Comparative Example 1 Invention Example 1 Invention Example 2 Invention Example 3 G'[kPa] 102.97 100.83 96.72 99.70 ML,dNM 1.10 1.13 1.16 1.19 MH,dNM 10.72 10.49 10.54 10.65 T90,m:s 12:24 12:06 12:47 14:31 Mooney viscosity 32.7 33.5 34.1 34.4 Mooney Scorch 29.03 27.78 27.48 31.98
[0063] The Payne effect refers to the phenomenon that the storage modulus of filled rubber decreases sharply with the increase of dynamic strain under small deformation dynamic conditions. G' is usually used to characterize the degree of aggregation of fillers and the filler network structure. The lower G' is, the weaker the Payne effect is and the better the filler dispersion is. The G' of the inventive example is significantly smaller than that of the comparative example, indicating that the degree of filler aggregation and networking of the rubber material of the inventive example is weakened. It is analyzed that the amount of carbon black in the inventive example is reduced, part of the carbon black is replaced by white carbon black, white carbon black reacts with rubber after silanization reaction with silane coupling agent to form a binding glue, and the sulfur in the coupling agent reacts with the rubber molecular chain to form a small amount of monosulfide, disulfide, polysulfide or polysulfide covalent bonds. The two work together to prevent filler aggregation and the formation of filler network structure. The bonding force between filler and rubber is enhanced, and the dispersion of filler in the matrix is significantly improved. This is consistent with the reduction of friction between filler-filler and filler-rubber, and the change trend;
[0064] Compared with the comparative example, the curing time of the inventive example is prolonged. Analysis shows that white carbon black is an inorganic filler, and the surface hydroxyl and siloxane groups have a relatively strong adsorption layer, which adsorbs small organic molecules and has a special adsorption effect on aniline, etc. It can also strongly adsorb the accelerator in the rubber compound, thereby delaying the curing;
[0065] Principle analysis: The surface energy of rubber hydrocarbon polymers is low, while the surface energy of carbon black is high. The increase in the amount of carbon black will lead to a decrease in the rubber content and an increase in the content of high surface energy substances. Under certain stress and temperature, the vulcanized rubber with a large amount of carbon black loses a lot of energy, and the energy is converted into heat to increase the temperature. The increase in the amount of carbon black will enhance the interaction between filler-filler, rubber-rubber, and filler-rubber, and increase the compression fatigue temperature. Figure 1 As shown. However, due to the special chemical and physical properties of silica, the filler-filler interaction of the rubber compound with silica added is relatively weak, and the effect of reducing the compression fatigue temperature rise is more obvious;
[0066] This application proposes to reduce the dynamic heat generation of rubber from the perspective of filler. By adjusting the type of carbon black in the reinforcement system, optimizing the use of large-particle carbon black, increasing white carbon black, and using an appropriate amount of silane coupling agent, the purpose of maintaining the physical properties of the rubber while reducing the heat generation of the rubber is achieved. The use of white carbon black reduces rolling resistance without affecting the tire's anti-skid performance. Compared with tires filled with ordinary carbon black only, white carbon black tires not only reduce fuel consumption, but also have excellent traction performance. White carbon black is not as easy to combine with polymers as carbon black, and needs to be used in combination with silane coupling agents to enhance the combination between white carbon black and polymers, improve the dispersibility of white carbon black, and reduce the hysteresis loss of the rubber.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A sidewall rubber composition for reducing tire rolling resistance, characterized in that: Calculated by weight, it includes: 40-60 parts of cis-1,4 polyisoprene, 40-60 parts of butadiene rubber, 20-40 parts of carbon black, 10-20 parts of new white carbon black, 0-2 parts of silane coupling agent, 1-3 parts of stearic acid, 2-7 parts of zinc oxide, 1.5-3.5 parts of antioxidant 6PPD, 0.5-3 parts of antioxidant TMQ, 2 parts of antioxidant 31000, 1.5-2 parts of oil-extended sulfur powder and 0-1.5 parts of accelerator.
2. The sidewall rubber composition for reducing tire rolling resistance according to claim 1, characterized in that: The butadiene rubber is 50 parts.
3. The sidewall rubber composition for reducing tire rolling resistance according to claim 1, characterized in that: The carbon black is low hysteresis carbon black.
4. The sidewall rubber composition for reducing tire rolling resistance according to claim 3, characterized in that: The specific surface area of carbon black is between 11-22g / kg, and the oil absorption value is between 90-10010-5m3 / kg.
5. The sidewall rubber composition for reducing tire rolling resistance according to claim 1, characterized in that: The novel silica is fumed silica.
6. The sidewall rubber composition for reducing tire rolling resistance according to claim 5, characterized in that: The nitrogen adsorption specific surface area of fumed silica is between 15-35m2 / g, and the silicon dioxide content is above 95.0%.
7. The sidewall rubber composition for reducing tire rolling resistance according to claim 1, characterized in that: The silane coupling agent is 1%-10% by weight of white carbon black.
8. A tire made by using the sidewall rubber composition for reducing tire rolling resistance according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-performance tire tread rubber and preparation method thereof
CN109181027A